Bergapten inhibits NLRP3 inflammasome activation and pyroptosis via promoting mitophagy - Luo Tong; Jia Xin; Feng Wan-di; Wang Jin-yong; Xie Fang; Kong Ling-dong; Wang Xue-jiao; Lian Rui; Liu Xia; Chu Ying-jie; Wang Yao; Xu An-long (Acta Pharmacologica Sinica, 2023)
Inhibition of NLRP3 inflammasome activation produces potent therapeutic effects in a wide array of inflammatory diseases. Bergapten (BeG), a furocoumarin phytohormone present in many herbal medicines and fruits, exibits anti-inflammatory activity. In this study we characterized the therapeutic potential of BeG against bacterial infection and inflammation-related disorders, and elucidated the underlying mechanisms. We showed that pre-treatment with BeG (20 μM) effectively inhibited NLRP3 inflammasome activation in both lipopolysaccharides (LPS)-primed J774A.1 cells and bone marrow-derived macrophages (BMDMs), evidenced by attenuated cleaved caspase-1 and mature IL-1β release, as well as reduced ASC speck formation and subsequent gasdermin D (GSDMD)-mediated pyroptosis. Transcriptome analysis revealed that BeG regulated the expression of genes involved in mitochondrial and reactive oxygen species (ROS) metabolism in BMDMs. Moreover, BeG treatment reversed the diminished mitochondrial activity and ROS production after NLRP3 activation, and elevated the expression of LC3-II and enhanced the co-localization of LC3 with mitochondria. Treatment with 3-methyladenine (3-MA, 5 mM) reversed the inhibitory effects of BeG on IL-1β, cleaved caspase-1 and LDH release, GSDMD-N formation as well as ROS production. In mouse model of Escherichia coli-induced sepsis and mouse model of Citrobacter rodentium-induced intestinal inflammation, pre-treatment with BeG (50 mg/kg) significantly ameliorated tissue inflammation and injury. In conclusion, BeG inhibits NLRP3 inflammasome activation and pyroptosis by promoting mitophagy and maintaining mitochondrial homeostasis. These results suggest BeG as a promising drug candidate for the treatment of bacterial infection and inflammation-related disorders.